A Seventeen-year-old Boy Patient with Lupus Nephritis as a Complication of Systemic Lupus Erythematosus (SLE) at Sanglah General Hospital, Bali, Indonesia: a Case Report - Anak Agung Ngurah Subawa (Journal of Global Pharma Technology, 2016)
Background: The systemic lupus erythematosus (SLE) is an autoimmune disease with various clinical manifestations. SLE indicated by the presence of autoantibodies to the nucleus components and immune complex deposits. Prevalence ratio of SLE is higher in women than in men, but male patients seem to have a higher frequency of symptoms and more aggressive disease. So, this case study aims to evaluate A seventeen-year-old boy patient with lupus nephritis as a complication of Systemic Lupus Erythematosus (SLE) based on laboratory evaluation. Case Description: A seventeen-year-old male patients referred to the emergency department in Sanglah General Hospital with swelling on both eyelids and legs for two weeks before admission. The patient has high blood pressure, discolouration of urine and significant weight gain about 14 kilograms in two weeks due to swelling. Several examinations performed and the results were indicating anaemia, proteinuria, hematuria, hypoalbuminemia, high BUN and creatinine level, hyperkalemia, hyperphosphatemia and high titer of ANA-IF and anti-ds-DNA level. The patient diagnosed with lupus nephritis and treated with antihypertension and diuretic. Conclusion. The most common complication of SLE is lupus nephritis, and its prevalence varies significantly by region, race and tribe. Although overall improvements in the treatment of SLE patients have increased in kidney survival rates, the prognosis remains unsatisfactory. Early detection and diagnosis should be done so that the patient’s condition worsens not occur because the late diagnosis of LN can increase the risk of End-Stage Renal Disease.Keywords: Autoimmune Disease, Lupus Nephritis, Systemic Lupus Erythematosus.